Self-Esteem Levels of the Indebted Lower-Income Group and the Role of Organizations in the Plantation Sector - TOTO NGADIMAN, DICKY WIWITTAN; Yacoob, Salmy Edawaty; Wahid, Hairunnizam (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
High level self-esteem is a very important human need. Many studies have found that one's behaviour are somewhat influenced by their level of self-esteem. According to Maslow's Theory, if this need is not fulfilled, an individual may experience failed identity, unbalanced personality, lack self-confident and quick to quit, and sometimes it may lead to social and criminal problems. Some individual consider money not only as instrument to meet the basic needs but also for the high level needs such as self-esteem. Due to poverty and lack of income, low-income individuals are seen as less successful and reluctant to socialize with others. This group is also often associated with debt to meet their basic needs. However, the current scenario also shows that debt is not only associated with the purpose of purchasing basic needs but also for higher needs such as to increase self-esteem. Previous study found that there is a link between organizational supports towards self-esteem and suggested that organizations need to enhance the rewarding system that is more focuses on individual self-esteem. Hence, this study is conducted to see the level of self-esteem of the B40 Muslim borrower and evaluate the level of organizational support in raising the Muslim B40's self-esteem. Respondents in this study consisted of settlers and general Muslim workers who belong to the category of low-income households residing and working in Felda. The findings show that their level of self-esteem as well as the role of employers is at a moderate level. Implicitly, this study can help Felda management, employers and certain authorities in Malaysia to draw up human development plan to empower their self-esteem. Keyword: self-esteem, debt, low income, organizational support